Soil Moisture Variations in Response to Precipitation Across Different Vegetation Types on the Northeastern Qinghai-Tibet Plateau - Dai, Licong; Fu, Ruiyu; Guo, Xiaowei; Du, Yangong; Zhang, Fawei; Cao, Guangmin (Frontiers in Plant Science, 2022)
An understanding of soil moisture is crucial for hydrological modeling and hydrological processes, An understanding of soil moisture is crucial for hydrological modeling and hydrological processes, however few studies have compared differences between the dynamics of soil moisture content, and soil moisture response to precipitation infiltration under different types of vegetation on the Qinghai-Tibet Plateau (QTP). In this study, time-domain reflectometry (TDR) were used for continuous soil volumetric soil moisture measurements during 2015-2016, with aim to explore the variations in soil moisture and its response to precipitation infiltration across two vegetation types (alpine meadow and alpine shrub). Our results show that temporal variations in soil moisture at the surface (0-20 cm) and middle soil layers (40-60 cm) were consistent with precipitation patterns for both vegetation types. However, there was a clear lag in the soil moisture response to precipitation for deep soil layers (80-100 cm). Soil moisture content was found to be significantly positively related to precipitation amount, and significantly negatively related to air temperature. Aboveground biomass was significantly negatively associated with surface soil moisture content (0-20 cm) during growing season. There were statistically significant differences between the soil water content of the surface, middle and deep soil layers for the two vegetation types. Soil moisture in the surface soil layer were significantly lower than in the deep soil layer for alpine shrub, and the converse was observed for alpine meadow. The maximum infiltration depth of alpine shrub was higher than of alpine meadow under extreme high precipitation event, indicated that the alpine shrub might less susceptible to surface runoff under extreme precipitation event. Furthermore, low precipitation amounts were not seen to affect precipitation infiltration for either vegetation type, while infiltration depth increased with precipitation for both vegetation types. Our results suggests that a series of small precipitation events may not have the same effect on soil moisture as the same total rainfall amount provided in a single large precipitation event.